2006
DOI: 10.1203/01.pdr.0000219172.16638.f9
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Birth Defects with Adult Intellectual Performance, Disability and Mortality: Population-based Cohort Study

Abstract: Infants born with birth defects have poorer outcomes in terms of mortality and disability, but the long-term intellectual outcome in children with birth defects is generally unknown. We assessed the long-term associations of various birth defects with mortality and disability, and evaluated whether high mortality and disability were reflected in impaired intellectual performance at age 18. In this nationwide cohort study, records of 9,186 males with and 384,384 without birth defects, registered in the Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 29 publications
2
35
0
1
Order By: Relevance
“…Individuals with cleft had higher odds of receiving the lowest grade and/or reduced odds of receiving high grades among subjects analyzed, along with strong evidence of a lower grade point average in comparison with the population as a whole. This study is congruent with other studies that have identified greater prevalence of cognitive dysfunction and learning difficulties, lower school achievements, and greater use of special education services in individuals with cleft in comparison with individuals without cleft (Broder et al, 1998;Nopoulos et al, 2002;Richman et al, 2005;Eide et al, 2006;Yazdy et al, 2008). Furthermore, this study supports the need to consider cleft type in studies of cognitive and educational outcomes (Richman, 1980;Richman and Eliason, 1984;Richman et al, 1988;Broder et al, 1998), with individuals with CP having the most negative outcome, followed by individuals with CLP, and those with CL being the least affected in comparison with the control group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Individuals with cleft had higher odds of receiving the lowest grade and/or reduced odds of receiving high grades among subjects analyzed, along with strong evidence of a lower grade point average in comparison with the population as a whole. This study is congruent with other studies that have identified greater prevalence of cognitive dysfunction and learning difficulties, lower school achievements, and greater use of special education services in individuals with cleft in comparison with individuals without cleft (Broder et al, 1998;Nopoulos et al, 2002;Richman et al, 2005;Eide et al, 2006;Yazdy et al, 2008). Furthermore, this study supports the need to consider cleft type in studies of cognitive and educational outcomes (Richman, 1980;Richman and Eliason, 1984;Richman et al, 1988;Broder et al, 1998), with individuals with CP having the most negative outcome, followed by individuals with CLP, and those with CL being the least affected in comparison with the control group.…”
Section: Discussionsupporting
confidence: 90%
“…Research has indicated that individuals with cleft can experience cognitive dysfunction, learning difficulties, and lower levels of school achievement (Richman and Eliason, 1982;Broder et al, 1998;Nopoulos et al, 2002;Richman et al, 2005;Eide et al, 2006). Research indicates that these deficiencies can be attributed to the type of cleft (Richman, 1980;Richman andEliason, 1982, 1984;Richman et al, 1988;Broder et al, 1998) or the severity of cleft (McWilliams et al, 1972;Fox et al, 1978;Nopoulos et al, 2002).…”
mentioning
confidence: 99%
“…They remain a major contributor of infant mortality and lifelong disabilities (Centers for Disease Control and Prevention (CDC), National Vital Statistics Report, ; Decoufle, Boyle, Paulozzi, & Lary, ). Compared to children without birth defects, children with birth defects are more likely to experience hospitalizations as well as neurologic and cognitive impairments (Arth et al, ; Decoufle et al, ; Eide, Skjaerven, Irgens, Bjerkedal, & Oyen, ; Petterson, Bourke, Leonard, Jacoby, & Bower, ).…”
Section: Introductionmentioning
confidence: 99%
“…Children with OFC also have lower achievement and increased special needs in academic settings (Goodstein, 1961; Strauss and Broder, 1993; Broder et al, 1998; Persson et al, 2012; Richman et al, 2012). Intelligence quotient (IQ) studies have shown that children with isolated OFC have lower mean scores than children without OFC, and this trend is apparent at young ages (12–24 months old) and early adulthood (Jocelyn et al, 1996; Eide et al, 2006; Persson et al, 2008). Evaluation of specific cognitive functions shows that the greatest deficit is in verbal IQ, and children with OFC may experience increased reading and language problems (Kommers and Sullivan, 1979; Richman et al, 1988; Collett et al, 2010a; Collett et al, 2010b).…”
mentioning
confidence: 99%